Circumcision Advances and New Perspectives - Zaghal, Ahmad; El Safadi, Ali (IntechOpen, 2023)
Male circumcision has been practiced since the dawn of human culture and may be performed for medical and non-medical reasons. Although a simple procedure, if not properly performed it may lead to minor or even serious complications, such as urethral or glanular injury. Circumcision is performed using various techniques, including the classic open technique, clamp technique, and laser /electrocautery technique, with various outcomes in terms of safety. The debate over the pros and cons of cultural circumcision continues, with experts in the field holding divergent opinions.The purpose of this book is to present an overview of the historical background of male circumcision and to describe different circumcision techniques.